حصر المتطفلات الحشرية المرافقة لحشرة حفار ساق التفاح Zeuzera pyrina(L) (Lepidoptera: Cossidae) في بعض بساتين التفاح في محافظة اللاذقية - أصلان, لؤي; بشير, عبد النبي; إبراهيم, جونار (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى تعريف المتطفلات الحشرية المرافقة لحشرة حفار ساق التفاح في بستاني تفاح في منطقتي عرامو وربيعة التابعتين لمحافظة اللاذقية خلال عامي 2007 و 2008 وتحديد نسبة التطفل والكثافة النسبية لكل نوع من المتطفلات. أظهرت النتائج وجود أربعة متطفلات حشرية مرافقة للحشرة في منطقتي الدراسة وهي:Pristomerus vulnerator, Diadegma terebrans, Hypercampus sp , والطفيل Copidosoma trunctellum. تراوحت نسبة التطفل بين (4.17 و29.06)% في ربيعة, وبين (16.1 و31.12)% في عرامو. كان المتطفل السائد في ربيعة C. trunctellum بنسبة 50%, وساد المتطفل P .vulnerator في عرامو بنسبة 42%. The main objective of the research involved identifying the associated parasitoids with Leopard moth in two apple orchards in Lattakia governorate ( Aramo and Rabiia ), and defining the percentage of parasitism and the relativity density for each parasitoid during 2007 and 2008. The results of this study showed that there were four parasitoids associated with Leopard moth in the two regions. These identified parasitoids were Pristomerus vulnerator, Diadegma terebrans, Hypercampos sp, and Copidosoma trunctellum. The percentage of parasitism ranged from 4.17 to 26.06 % in Rabiia, and from 16.1 to 31.12% in Aramo. C.trunctellum was the predominant parasitoid in Rabiia region (50%), P. vulnerator was the predominant parasitoid in Aramo region (42%).